ORALITY AND PRESENCE OF DEATH IN TAITA CRISTO (1964) BY ELEODORO VARGAS VICUÑA - Mostacero Castillo, Jonathan (2022)
Eleodoro Vargas Vicuña is considered one of the greatest storytellers of the generation of the 50s and of Peruvian literature in a general sphere. In this study, the Taita Cristo (1964) account will be analyzed from the perspective of death. In this sense, the previous aspect will be taken as knowledge related to the oral popular tradition, evoked in the dialogues of the characters and the plot development. Likewise, the function of orality will be highlighted, a prominent issue in the author's book due to its ability to articulate different themes, including the particular ritual nature of death seen from the Andean perspective. For our purposes, the stories “El tuco y la paloma” and “El desconocido” will be examined.